Дослідження печери Луг у селі Винятинці на Тернопільщині - Олійник, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
The article is dedicated to investigations of cave Lug, carried out during 2005–2006 years by Regional municipal museum in Zalischyky in village Vyniatyntsi, Zalischykyi district, Ternopil’ region. Complex of artifacts of Goligrads’ka culture, Slavic, Old Russian periods and Late Middle Age were found there.